Enhancing Mezcal Production Efficiency by Adding an Inoculant of Native Saccharomyces cerevisiae to a Standardized Fermentation Must - Armando H. Holguín-Loya; Adriana E. Salazar-Herrera; Nicolas O. Soto-Cruz; Manuel R. Kirchmayr; Christian A. Lopes; Juan A. Rojas-Contreras; Jesús B. Páez-Lerma (Foods, 2025)
All traditional mezcal producers use artisan methods to produce mezcal. The low technological development in the elaboration processes results in low yield and high residual sugar concentration. First, this work optimized the concentration of initial sugars and yeast-assimilable nitrogen (YAN) in Agave durangensis juice fermentation at the laboratory level. A yield near 0.49 g EtOH/g sugar and a productivity of 1.54 g EtOH/L*h was obtained with an initial sugar concentration of 120 g/L and a YAN concentration of 0.227 g/L. Only Saccharomyces cerevisiae was found after 24 h of incubation at laboratory level, using MALDI-TOF identification. Agave durangensis heads crushed by the artisan process were used to test the inoculant performance. A mezcal yield of 11.6 kg agave/L of mezcal was obtained using the S cerevisiae inoculant and nitrogen addition, which was significantly different (p < 0.05) from other treatments. The population dynamics during fermentation were analyzed through isolation and identification using MALDI-TOF. Several yeast species (Pichia kluyveri, Torulaspora delbrueckii, Zygosaccharomyces bailii, and Saccharomyces cerevisiae) were found at the beginning of fermentation. Nonetheless, only S. cerevisiae was found at the end of fermentation. The implantation of the inoculant used was confirmed through the comparative analysis of amplification patterns of the GTG5 microsatellite of the strains identified as S. cerevisiae, finding that the inoculated strain proportion was greater than 80% of the yeast population. A technological alternative to increase the efficiency of the process is combining the addition of YAN and the inoculation of the native S. cerevisiae, which was isolated from artisan alcoholic fermentation of agave to produce mezcal.